The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.4103/2231-0738.114856
|View full text |Cite
|
Sign up to set email alerts
|

Co-existence of child and adolescent obesity and thinness in a city in Nigeria: Comparison of results derived from different reference standards

Abstract: Objectives:The nutrition transition in developing countries has resulted in the "nutrition paradox" where both under-and over-nutrition exist in the same population. This phenomenon is scarcely reported in Nigeria. The prevalence of thinness and overweight/obesity was therefore studied in Umuahia, Nigeria using two international references and the results compared. Subjects and Methods: A total of 1911 children and adolescents (51.3% females) were recruited and anthropometric data obtained from them using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Differences of prevalence of overweight and obesity between genders have been related to geopolitical and cultural conditions. [20] However, a study conducted in Delhi [17] among affluent adolescent school children, found a higher prevalence of obesity in males in comparison to females. In another study in Ludhiana, [12] no significant difference in the prevalence of overweight and obesity was found between the two genders.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Differences of prevalence of overweight and obesity between genders have been related to geopolitical and cultural conditions. [20] However, a study conducted in Delhi [17] among affluent adolescent school children, found a higher prevalence of obesity in males in comparison to females. In another study in Ludhiana, [12] no significant difference in the prevalence of overweight and obesity was found between the two genders.…”
Section: Discussionmentioning
confidence: 95%
“…The coexistence of thinness and overweight adolescents has also been reported in a study in Nigeria. [17] Kapil et al, [9] reported the prevalence of obesity in adolescent school-going children of affluent Indian families to the tune of 7.4% and overweight 23.1%.…”
Section: Discussionmentioning
confidence: 99%
“…An earlier cross-sectional study in Umuahia, Nigeria, using the same diagnostic tool as used in this study reported a thinness prevalence of 17.3% in males and of 15.5% in females [2]. These values are closer to the values reported in Schools 1 (very affordable; rural) and 2 (affordable; urban-poor), but considerably higher than values reported for Schools 3 (expensive; urban-middle income) and 4 (very expensive; urban-rich).…”
Section: Discussionmentioning
confidence: 98%
“…In Nigeria, there are reports of high prevalence of both under- and over-nutrition, even in the same locality [1,2]. This double burden of malnutrition in societies experiencing nutrition transition calls for deliberate holistic health policy action to cater for the needs of populations at risk of nutritional challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Meeting the nutritional requirements of adolescents may be a crucial move towards ending the cycle of malnutrition, long-term illnesses, and destitution that passes from one generation to another. Conversely, investigations into the causal factors of malnutrition among adolescents have been conducted in various regions, including Ibadan [1], Abuja [10], Aba [13], Kano [14] and Umahia [15]. However, it is noteworthy that no analogous studies have been undertaken in Asaba, Delta State.…”
Section: Introductionmentioning
confidence: 99%